O império escravista - Capela, José (Africana Studia, 2020)
The seizure of slaves was one of lhe early and crucial motivations for lhe Discoveries Age. Slaveocracy as an integrating system of colonization, slavery as a way of production and lhe availability of forced labour were the nucleus of the Portuguese colonial em pire. If these were the essential means for the building of lhe Empire, slaveocrat is the proper name for it.